The Changing Colors of Maple Hills: Intersections of Culture, Race, Language, and Exceptionality in a Rural Farming Community. (March 2016) - Scanlan, Martin
This case describes Maple Hills Elementary, a K-8 school in a rural farming community of the Midwest. As a community, Maple Hills has historically experienced a narrow range of diversity across race, ethnicity, language, and religion. Residents have predominantly been White, with German and English heritage, speak English as a mother tongue, and identify as Protestant Christian. In the last decade, Maple Hills has experienced an influx of immigrants from several nations leading to a confluence of issues in Maple Hills Elementary involving culture, language, and special education. In this case, one immigrant mother begins asking hard questions that force the teachers and principals to begin to question their assumptions and practices regarding how student support services are delivered.